OPTIMASI QUERY DATABASE WEBSCRAPING PADA JURNAL SINTA - selva indah nurhafida (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
In Indonesia, there is the SINTA (Science and Technology Index) which is the official platform used to measure the performance of research and scientific publications made by Indonesian academics. However, not all national journals that have been accredited by the field of library science present correct and complete information on their websites. The database is more efficiently used for data storage because it has the ability to connect between data and is easier to develop. In this study, we try to optimize the query for searches that can display recommended data for the search for the SINTA journal with the query index method. The results obtained are that the query method requires less time, which is 0.15 seconds compared to using the usual query method with a load time of 6.00 seconds. The number of accredited at each level of SINTA is 118 units for S1 Accredited, 949 S2 Accredited, 1296 S3 Accredited, 2391 S4 Accredited, 1921 Accredited S5, and 266 Accredited S6. the number of accredited at each level of SINTA, namely for S1 Accredited as many as 118, S2 Accredited as many as 949 units, S3 Accredited as many as 1296 units, S4 Accredited in 2391 units, S5 Accredited in 1921 units, and S6 Accredited in 266 units.